AN ANALYSIS OF THE ATTITUDINAL, CONTEXTUAL AND GENDER PERSPECTIVES OF THE ENTREPRENEURIAL INTENTIONS AMONG INDONESIAN MILLENNIALS (Malaysian Management Journal, 2019)
The present study was designed to analyse the entrepreneurial intentions of the Indonesian millennials in Jambi City which are associated with the attitudinal, contextual and gender perspectives. This research focused on the millennial generation, namely students who will enter the labour market in the future. Data were collected from the surveys on millennials in Jambi City and analysed using the descriptive statistical tools and Structural Equation Modelling (SEM). The results indicate several factors: Firstly, the awareness level of gender equality of the millennials in the area is relatively low. There are still around a third of them who are gender-biased on the aspect of personality traits and gender roles in public sector jobs (nondomestic works). The proportion is even greater on the aspect of gender roles in domestic work. Over two-thirds of the millennials have gender-biased perceptions. Secondly, the entrepreneurial intentions of these students are relatively high. It shows that they have strong potentials to become young entrepreneurs in the future. Thirdly, the attitude and contextual factors have significant influence on the millennial entrepreneurial interests in Jambi City. The gender factor, however, does not show a significant impact as a direct influence as well as a variable moderating the influence of attitude and contextual factors.